The Role of Self-Efficacy in Students’ Writing Ability (A Case Study at Second Grade Students of a Senior High School in Indramayu) - Yulianawati, Ida (Vision: Journal for Language and Foreign Language Learning, 2019)
This case study aimed at investigating the role of self-efficacy in students’ recount text especially in the area of writing as one of the most difficult skills in learning English. Writing difficulties faced by the students are not only based on their cognitive skill but also their own efficacy beliefs. Three problems can be found related to self-efficacy beliefs in English writing. They are related with confidence to write anxiety, and the third problem is about the students’ interest. The participants of this study are three students from a Senior High School in Indramayu. The data were obtained from three data collection: questionnaire, writing test, and also the interview. The result of this study shows that the participants of this study perceived mastery experience accounted for the greatest proportion in their writing ability. It can be seen from how students rate their confidence and given overall feelings about the way to write successfully. Social persuasions and physiological states also were influential while working on writing. Meanwhile, the common experience did not predict too much in students' writing ability. Ultimately, the results of this research concluded that self-efficacy has an important role in students’ ability in writing.